Advanced triaxial technologies and modelling parameters - Correia, A. Gomes (2008)
Sociedade Portuguesa de Geotecnia, Universidade do Minho, Instituto Superior Técnico, LNEC, FCT-UNL, FCT, RAVE, REFER